2020
DOI: 10.4018/ijwltt.20200701.oa1
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Assessment Approaches and Quality Product Design Within Web-Based Learning Environments

Abstract: The aim of the present study is to identify the impact of the alternative web-based self and peer assessment approaches on improving the quality of student educational projects. In this context, a study was carried out during the second semester of the 2017-2018 academic year among 48 postgraduate students at King Faisal University. Results indicated that both self and peer-assessment approaches are effective when assessing the quality of educational products. The results also showed that the extent of student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Considering types of evaluation, the responders practiced evaluation by a teacher more often than others, while they sometimes used self, peer and group evaluation (Figure 9). The results of the research by Ahlam Mohammed Al-Abdullatif devoted to the alternative confirmed the fact that the extent of student experience with the selfassessment affects their credibility and objectivity [8]. Formative assessment is based on critical feedback, which is needed by all the participants of the educational process.…”
Section: Figure 7 the Respondents' Opinions About Involvement Of Students In Choosing Alternative Assessment Toolsmentioning
confidence: 74%
“…Considering types of evaluation, the responders practiced evaluation by a teacher more often than others, while they sometimes used self, peer and group evaluation (Figure 9). The results of the research by Ahlam Mohammed Al-Abdullatif devoted to the alternative confirmed the fact that the extent of student experience with the selfassessment affects their credibility and objectivity [8]. Formative assessment is based on critical feedback, which is needed by all the participants of the educational process.…”
Section: Figure 7 the Respondents' Opinions About Involvement Of Students In Choosing Alternative Assessment Toolsmentioning
confidence: 74%
“…The effectiveness of using the e-generator system in increasing students' self-efficacy is proven through this research. The use of digital technology in learning makes it easier for students to access learning materials more freely [27]- [29]. The student experience will be better if the learning media used is by their expectations.…”
Section: 4mentioning
confidence: 99%
“…Teacher evaluations, sometimes called traditional evaluation systems, have some drawbacks (Meihami & Esfandiari, 2020). Teachers also make decisions regarding the quality of students' responses do not measure all aspects of student learning (Al-Abdullatif, 2020;Meihami & Esfandiari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the shortcomings of the teacher's assessment, alternative assessment techniques that are effective and influential must evaluate students' educational development. Alternative reviews have been found to benefit the instructional process because they include procedures and practices easily integrated into student activities (Al-Abdullatif, 2020;Iraji et al, 2016). Students' participation in the assessment process promotes critical skills such as responsibility, assessment, and independence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation